Marker chromosomes of the long arm of chromosome 1 in endometrial carcinoma - Fujita, H; Wake, N; Kutsuzawa, T; Ichinoe, K; Hreshchyshyn, M M; Sandberg, A A (Cancer genetics and cytogenetics, 1985)
Cytogenetic studies were performed on endometrial specimens of four patients with hyperplasia, six with adenocarcinoma, and one with a mixed mesodermal tumor. Except for one cell, all 65 cells from the hyperplastic specimens had a normal female karyotype. However, a total of 92 cells from the five adenocarcinoma specimens had chromosome abnormalities, though all 20 cells from a specimen of a well differentiated adenocarcinoma showed a normal karyotype. The chromosome number and morphology of the aneuploid cells had minimal changes. The modal number of chromosomes was pseudodiploid in one case and hyperdiploid in four cases. Three kinds of structural abnormalities involving chromosomes #1 were identified to be of clonal origin: del(1p21) in two cases, tdic(1;16)(p21;q24) in one case, and i(1q) markers in two cases. Because the carcinoma cells had two chromosomes #1 of normal morphology, the presence of the marker chromosome led to partial trisomy or tetrasomy of the long arm of chromosome #1. This involvement may be assumed to represent a karyotypic change characteristic of some adenocarcinomas of the endometrium. Complex karyotypes with many rearranged chromosomes were observed in cells from the mixed mesodermal tumor. The karyotypic differences between endometrial carcinoma and the mixed medodermal tumor suggest that the genesis (and its mechanism) of the former may differ from that of the latter.